Germany : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper attempts to analyze the end-point problem and improve the quality of potential GDP estimates for Germany. It projects that Germany's potential GDP growth will slow over the coming decade, mainly because of declining labor input. The paper focuses on a long-term fiscal scenario for Germany based on current policies. The paper also attempts to construct a preliminary public sector balance sheet for Germany, and analyzes the performance of its nonfinancial corporate sector.